To Glide or not to Glide.... Response to Havriluk's Comment on "Arm coordination and performance level in the 400-m front crawl" - Schnitzler, C.; Seifert, L.; Chollet, D. (Research Quarterly for Exercise and Sport, 2012)
We recently published an article on arm coordination and performance level in 400-m front-crawl swimming in Research Quarterly for Exercise and Sport (Schnitzler, Seifert, & Chollet, 2011). The index of coordination (IdC) was used to quantify interarm coordination. Our results showed that expert swimmers exhibited lower IdC than recreational swimmers over a 400-m trial. In addition to criticizing various methodological points, Havriluk (2012) challenged our conclusion that catch-up could be an efficient model of coordination and instead suggested that it might lead to injuries. An important point in this debate, however, is that our definition of catch-up coordination may differ from the one proposed by Havriluk (2012), which would explain why we consider catch-up coordination to be the dominant mode of coordination used by expert swimmers during training sessions.